Perspectives for Sustainable Animal Production in Central America - Vargas Leitón, Bernardo (2000)
TOPICS •Human Development •Demographic trends •Land use •Environmental degradation •Economic development •Food Balance •Productivity •Trade •Implications for SAP •RESAP